Efeitos do dantrolene sódico e succinato de metilprednisolona na neuroproteção e morte celular, na medula espinhal de ratos submetidos a trauma compressivo agudo - Isabel Rodrigues Rosado (2011)
The aim of the present study was to evaluate the effects of dantrolene sodium, methylprednisolone, and their association in the treatment of rats subjected to compressive acute spinal cord injury. Therefore, 25 Rattus norvegicus were equally distributed into five groups. In G1 (negative control group), the animals were submitted to dorsal laminectomy of the T12 vertebra and received 0,9 % saline. In the other groups, in addition to laminectomy, the animals were subjected to compressive spinal cord injury, G2 (positive control group) received 0,9 % saline, G3 (SM) 30mg/kg of methylilprednisolone, G4 (SM/DS) 10mg/Kg of dantrolene sodium and 30mg/kg of methylprednisolone, and the G5 (DS) 10mg/kg of dantrolene sodium. The animals were clinically evaluated using the BBB test. The animals were euthanized eight days after injury and the spinal cords were collected. Cranial and caudal sections to the epicenter were obtained for morphological evaluation (HE), for immunohistochemical staining with Anti-NeuN antibody, and for TUNEL staining. No significant statistical differences were found between groups G2, G3, G4, and G5 in clinical recovery determined by the BBB test, means of intact neurons stained with Anti-NeuN antibody and TUNEL stain cells (P<0,05). Concluding, methylprednisolone, dantrolene sodium and the association of these two drugs have not been able to promote motor function improvement, and to reduce neurons and glia cells death, in rats subjected to the present experimental model of acute compressive spinal cord injury, with evaluation being carried out eight days after trauma